Epileptogenic Zone Location of Temporal Lobe Epilepsy by Cross-Frequency Coupling Analysis - Liu, Xiaotong; Han, Fang; Fu, Rui; Wang, Qingyun; Luan, Guoming (Frontiers in Neurology, 2021)
Epilepsy is a chronic brain disease with dysfunctional brain networks, and electroencephalography (EEG) is an important tool for epileptogenic zone (EZ) identification, with rich information about frequencies. Different frequency oscillations have different contributions to brain function, and cross-frequency coupling (CFC) has been found to exist within brain regions. Cross-channel and inter-channel analysis should be both focused, because they can help analyze how epilepsy networks change as well as localize the EZ. In this paper, we analyzed long-term stereo-electroencephalography (SEEG) data from 17 patients with temporal lobe epilepsy. Single-channel and cross-channel CFC features were combined to establish functional brain networks, and the network characteristics under different periods and the localization of EZ were analyzed. It is shown that theta-gamma phase amplitude coupling (PAC) within the electrodes in the seizure region increased during the ictal (p<0.05). And theta-gamma and delta-gamma PAC of cross-channel were enhanced in the early and mid-late ictal, respectively. It is also found that strong cross-frequency coupling state between channels of EZ in the functional network during the ictal, along with a more regular network than interictal. The accuracy rate of EZ localization was 82.4%. Overall, the combination of single-channel and multi-channel cross-band coupling analysis can help identify seizures and localize EZ for temporal lobe epilepsy. Rhythmic coupling reveals a relationship between the functional network and the seizure status of epilepsy.